2006
DOI: 10.5424/sjar/2006042-188
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sublethal exposure to triflumuron on the biological performance of Tetranychus urticae Koch (Acari: Tetranychidae)

Abstract: Effects of sublethal exposure to triflumuron on the biological performance of the two-spotted spider mite Tetranychus urticae Koch were analysed under laboratory conditions. Survivorship was affected by the compound. Triflumuron caused a reduction both in the percentage of eggs that developed to adults and in the survival of adult stage. Triflumuron also affected the fecundity. The net reproductive rate (R 0), the intrinsic rate of increase (rm), and the finite rate of increase (l) of treated females were lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
(6 reference statements)
2
4
0
1
Order By: Relevance
“…Physiological effects in the parent generation resulted in decreased survival of offspring. Sáenz‐De‐Cabezón et al (2006) revealed a decrease in survival trend, gross reproductive rate, net reproduction rate and intrinsic rate of increase of Tetranychus urticae (Koch) (Acari: Tetranychidae) which had been treated with triflumuron, as an IGR. In the study by Yin et al (2008), LC 25 and LC 50 concentrations of spinosad decreased intrinsic rate of increase, net reproduction rate, gross reproduction rate and increased doubling time in P. xylostella.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological effects in the parent generation resulted in decreased survival of offspring. Sáenz‐De‐Cabezón et al (2006) revealed a decrease in survival trend, gross reproductive rate, net reproduction rate and intrinsic rate of increase of Tetranychus urticae (Koch) (Acari: Tetranychidae) which had been treated with triflumuron, as an IGR. In the study by Yin et al (2008), LC 25 and LC 50 concentrations of spinosad decreased intrinsic rate of increase, net reproduction rate, gross reproduction rate and increased doubling time in P. xylostella.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Mahmoudvand et al (2011b) recently reported decreases in the intrinsic rate of increase (rm), net reproductive rate (R0), and gross reproduction rate (GRR) along with an increase in the doubling time (Dt) of P. xylostella after exposure to hexaflumuron. Similarly, Sáenz-de-Cabezón et al (2006) stated that rm and λ of Tetranychus urticae (Koch) (Acari: Tetranychidae) decreased after being treated with the IGR triflumuron. Wang et al (2008) remarked that biological parameters of Myzus persicae (Sulzer) (Hom.…”
Section: Discussionmentioning
confidence: 99%
“…Esto significa que las colonias que estuvieron expuestas a las concentraciones de flufenoxuron disminuyeron las tasas intrínsecas de crecimiento; resultados que con anterioridad fueron previstos por Wrensch (1985). Por su parte Saenz- de-Cabezón (2006) indicó que el triflumuron aplicado en disco de frijol a una concentración de 1gL-1 de Alsystin (250 g de triflumuron por Kg -1 ) redujo los valores de r m en un 38.8 %; en tanto que Marcic (2007) estudió el comportamiento poblacional de T. urticae a concentraciones subletales de spiridiclofen y registró una reducción de los valores de r m con respecto al testigo de 17.7 y 93.8% a concentraciones de 6 y 12 mgL -1 , respectivamente. Tiempo de generación (T G ).…”
Section: Resultados Y Discusiónunclassified